Training of Competitive Graduates Based on the Educational Standard of the ITMO University - A. A. Shekhonin; A. O. Voznesenskaya; A. V. Bakholdin; O. A. Gavrilina (Высшее образование в России)
The paper presents the concept, structure and features ofITMOUniversity’s independently established educational standard of a new generation. The standard has been developed on the basis of Federal State Educational Standard of Higher Education 3++, professional and international standards of engineering education, foresight forecasts of world scientific and technological development. The harmonious intellectual, cultural and moral development, as well as the formation of a professionally competitive personality is ensured by the implementation in the educational programs of the ITMO Code. TheITMOUniversityhas created mechanisms for the formation of actual requirements for the preparation of competitive professionals demanded at an international level. The authors propose the design and implementation system of the educational programs based on integration of the fundamental classical technical education, enhanced development of the universal, common and professional competencies, and extended implementation of the modern theoretical and applied practice-oriented researches, which are supported an active participation of industrial companies and research organizations in educational activities. An interdisciplinary content of educational programs together with orientation to individualization of education and introduction of advanced educational technologies including design, digital, network etc. provides a stable technology platform to achieve the standard requirements for learning outcomes.